Analysis of growth and phenology in biotypes of Raphanus raphanistrum susceptible and resistant to ALS-inhibiting herbicides - Fruet D.L.* (2024)
© (2024), (Universidade Federal do Ceara). All rights reserved.The resistance of a weed to a herbicide may be accompanied by an ecological disadvantage, which can hinder the establishment of resistant biotypes when the herbicide is not used. The aim of this study, therefore, was to evaluate the growth and phenology of two biotypes of Raphanus raphanistrum, one susceptible and the other resistant to ALS inhibitors. The research was carried out from August to December 2020, conducting two simultaneous experiments, with the susceptible and resistant biotypes grown as single crops or together with wheat. The parameters under evaluation were plant height, number of leaves, leaf area, shoot dry weight, growth rate, leaf area ratio, net assimilation rate, and phenology – determined using the BBCH scale. The results showed not only that development and growth in the sensitive biotype was greater compared to the resistant biotype, but also the precocity of the biotype. The only variable for which the resistant biotype was superior was root dry weight. Cross-resistance to ALS inhibitors resulted in a difference in the growth and phenology of the resistant biotype that should be better evaluated, as the populations present large genetic differences.